The impact of dominant ventricle morphology and accessory ventricle size on clinical outcomes after Fontan procedure. (3rd October 2022) - Padalino, M; Azzolina, D; Puricelli, F; Reffo, E; Cabrelle, G; Cavaliere, A C; Guariento, A; Castaldi, B; Biffanti, R; Vida, V; Disalvo, G
Abstract: Objectives: the physio-pathological role of the morphological ventricular dominance (left, FSLV; right, FSRV), and the hemodynamic contribute of an accessory ventricular chamber (AVC), in patients with functional single ventricle (FSV) after Fontan operation are still uncertain due to conflicting data. We analyzed a cohort of Fontan patients to assess and correlate such anatomical features to late clinical outcomes. Methods: We enrolled all patients after a Fontan procedure who underwent a cardiac magnetic resonance (CMR) and a cardiopulmonary exercise test (CPET) in the previous 3 years. Clinical, CMR and CPET data from the last follow-up visit were retrieved to analyze whether the size of any AVC and the morphological ventricular dominance (FSLV vs FSRV) were correlated with clinical outcomes (NYHA, need for reinterventions or cardiac transplantation, mortality, arrhythmias, liver disease and protein-losing enteropathy) and functional parameters (including FSV ejection fraction and presence of late gadolinium enhancement, LGE, on CMR and peak metabolic equivalents, pMETs, and peak oxygen consumption, pVO2, at CPET). All statistical tests were two tailed and significance was set at 0.05. Results: we enrolled 50 patients: 29 had FSLV (58%), FSRV in 21 (42%). Median age at evaluation was 19.5 years [IQR 15–26]; median follow-up was 16 years [4–42]. NYHA class III or IV was present in 6%, while 4 (8%) underwent a re-do Fontan, 2 (4%) entered transplantation waiting list and one of these received a transplant. 2 patients (4%) died at follow-up. Statistical analysis showed that the accessory chamber was larger (>20 cc/m 2 ) in FSLV than in FSRV (p=0.01). In the post-operative period, FSRV was associated with higher incidence of low-cardiac output syndrome (p=0.043). In the long-term, there was no statistically significant difference in major clinical outcomes or NYHA class between the two groups. FSLV was associated with a better cardiac function (median FSV ejection fraction 56% vs 52%; p=0.041), less extent of LGE [p = 0.022], better functional capacity expressed by METs (14.1 vs 12.3; p=0.01) and pVO2 (1.625 ml/min vs 1.233 ml/min; p=0.033). An AVC was detected in all: its size was <5 ml/m 2 in 31%, 5–20 ml/m 2 in 47%, and >20 ml/m 2 in 22%. A larger AVC was associated with higher need for postoperative ECMO support (p=0.007), while size of AVC was not associated to any statistically difference in clinical outcomes, cardiac function and functional capacity. Conclusions: In Fontan circulation, a FSLV is correlated to better clinical and functional outcomes when compared to FSRV. On the other side, an AVC appears to be not significantly related to any clinical disadvantage. However, the immediate postoperative course may be influenced negatively by the presence of a larger AVC. Funding Acknowledgement: Type of funding sources: None.